Synthesis, characterisation and functionalization of Hercynite nanoparticles for improved antibacterial activity - Swapnali Walake; Rutuja Gumathannawar; Suyog Mane; Rohit Shendkar; Avinash Rokade; Mandar Shirolkar; Yogesh Jadhav (Journal of Experimental Nanoscience)
Hercynite i.e.,FeAl2O4 is an earth-abundant spinel mineral with a cubic crystal structure and belongs to the normal spinel ferrites possessing optical absorption in the visible range as well as superior magnetic and thermal properties. Herein, we synthesized nanosized FeAl2O4 where the citric acid-mediated sol–gel auto-combustion method was employed to achieve its pure phase and studied its physicochemical properties. Furthermore, the superior colloidal dispersion stability of the FeAl2O4 nanoparticles was achieved required for antibacterial activity and standardised via post-synthesis surface functionalisation using amino-propyl-triethoxysilane (APTES). We further characterised the material using states of art characterisation techniques for their structural, morphological, optical and thermal properties. Finally, the antibacterial activity of pure and surface functionalised FeAl2O4 nanoparticles was investigated against the Escherichia coli (E. coli) strain. We observed good penetration of surface functionalised FeAl2O4 nanoparticles into the bacterial membranes due to the high degree of dispersion achieved via cationic surface charge. Conclusively, a key finding of this study is the enhanced antibacterial properties of surface functionalised FeAl2O4 nanoparticles for the concentration of 31 µg/mL compared to pure FeAl2O4 nanoparticles at 62 µg/mL. This study has great relevance in the area of wound healing and tissue regeneration in the future.